Synchrotron X-ray photoelectron spectroscopy study of sodium adsorption on vertically arranged MoS2 layers coated with pyrolytic carbon - Okotrub, Alexander V.; Fedorenko, Anastasiya D.; Makarova, Anna A.; Sulyaeva, Veronica S; Fedoseeva, Yuliya V.; Bulusheva, Lyubov G. (Beilstein Journal of Nanotechnology, 2025)
Hybrid materials consisting of molybdenum disulfide (MoS2) and graphitic-like carbon have great potential for practical application as anodes in high-performance sodium-ion batteries. In this work, to reveal the effect of carbon coating on the interaction of sodium with the MoS2 layers located vertically relative to the substrate, model experiments were carried out using synchrotron-radiation-induced X-ray photoelectron spectroscopy (XPS). Sodium vapor obtained by heating a sodium source was simultaneously deposited in vacuum on the surfaces of MoS2, pyrolytic carbon, and a hybrid sample obtained by transferring a pyrolytic carbon film onto the MoS2 film. According to XPS data, sodium easily penetrates into the space between the vertical layers of the uncoated film, and its interaction with MoS2 leads to the transformation of the original hexagonal structure into a distorted tetragonal one. Under the experimental conditions, sodium is unable to diffuse through the carbon film consisting of horizontally oriented graphene domains and is almost completely removed by annealing the sample at 773 K in ultrahigh vacuum. The presence of the underlying MoS2 film facilitates the diffusion of sodium through the graphitic coating, but not all of the deposited sodium reaches MoS2. As a result, the sodium-induced rearrangement of the carbon-coated MoS2 is less than that of the free MoS2 film, and annealing of the sodiated sample restores its structure. The obtained results demonstrate the important role of the graphitic coating in the development of viable MoS2-based electrodes for energy storage systems.
Keywords: graphitic coating; molybdenum disulfide film; Na adsorption/desorption; sodium vapor; XPS